The neutralizing role of IgM during early Chikungunya virus infection. - Chong-Long Chua; I-Ching Sam; Chun-Wei Chiam; Yoke-Fun Chan (PLoS ONE)
The antibody isotype IgM appears earlier than IgG, within days of onset of symptoms, and is important during the early stages of the adaptive immune response. Little is known about the functional role of IgM during infection with chikungunya virus (CHIKV), a recently reemerging arbovirus that has caused large global outbreaks. In this study, we studied antibody responses in 102 serum samples collected during CHIKV outbreaks in Malaysia. We described the neutralizing role of IgM at different times post-infection and examined the independent contributions of IgM and IgG towards the neutralizing capacity of human immune sera during the early phase of infection, including the differences in targets of neutralizing epitopes. Neutralizing IgM starts to appear as early as day 4 of symptoms, and their appearance from day 6 is associated with a reduction in viremia. IgM acts in a complementary manner with the early IgG, but plays the main neutralizing role up to a point between days 4 and 10 which varies between individuals. After this point, total neutralizing capacity is attributable almost entirely to the robust neutralizing IgG response. IgM preferentially binds and targets epitopes on the CHIKV surface E1-E2 glycoproteins, rather than individual E1 or E2. These findings provide insight into the early antibody responses to CHIKV, and have implications for design of diagnostic serological assays.